Heavy sulfur isotope of arc ultramafic cumulates revealed by S-rich apatite from the Dongwanzi intrusion, North China - Huan Jennifer Chang; Mei-Fu Zhou; Wen-Jun Hu; Shengbiao Yang; Jian-Feng Gao (Chemical Geology, 2026)

An investigation of an outbreak of Salmonella Typhimurium infections linked to alfalfa sprouts – United States, 2022 - Mardea Caulcrick-Grimes; Brianna K.D. Loeck; Patricia Homola; Tong-Jen Fu; Jonathan Burgos; Daniela Schoelen; Robert Literman; Evelyn Ladines; Annemarie Buchholz; Grace Tung; Natalie Smith; Bryan F. Buss; et al. (Food Control, 2026)

How to improve the environmental friendliness of the thermal power industry: A perspective on constructing cross-regional collaborative emission reduction mechanisms tailored to local conditions - Yuting Fu; Changhui Yang; Jennifer Shang; G.G. Hegde; Ling Wang (Sustainable Cities and Society, 2025)

Cyclosiloxane artifacts explain reported Henry’s law constants for nonvolatile fluorotelomer sulfonates - Sophia K. Nelson; Mitchell L. Kim-Fu; Mohammad Azizian; Jennifer A. Field (Journal of Hazardous Materials, 2025)

Sea level rise submergence simulations suggest substantial deterioration of Indian River Lagoon ecosystem services likely by 2050, Florida, USA - Randall W. Parkinson; Levente Juhasz; Shimon Wdowinski; Valerie Seidel; Jennifer Fu (Regional Environmental Change, 2025)

Future Shorelines: A Living Shoreline Site Selection and Design Decision Support Tool that Incorporates Future Conditions Induced by Sea Level Rise - Randall W. Parkinson; Levente Juhasz; Jinwen Xu; Zhaohui Jennifer Fu (Estuaries and Coasts, 2024)
Most living shoreline site selection and design decision support tools are based upon existing environmental conditions. We developed a web-based, geospatial tool called Future Shorelines that integrates high-resolution landscape elevation data and a matrix of locally derived NOAA Interagency Sea Level Rise Scenarios to characterize future conditions of submergence and shoreline translation induced by sea level rise. Once the practitioner selects a location of interest, sea level rise scenario (e.g., high), and target year (e.g., 2050), the tool will generate plan view and cross-sectional informational graphics specific to their choices. This information can then be paired with other menu options, like parcel ownership, to facilitate the planning and construction of nature-based shoreline stabilization solutions that (1) are located where opportunities for horizontal migration are optimized, (2) remain accessible for monitoring and maintenance, and (3) perform as intended over the design life of the installation. The tool’s menu options and the user interface were informed by project partner input solicited during numerous workshops convened over the duration of the 2-year project. This coproduction created a product that was familiar to the end user and therefore increased the likelihood that it would be utilized by them during the planning and design of living shoreline projects. Although developed for use in the Indian River Lagoon, located along the east-central Florida coast, it can be seamlessly replicated for application in other coastal regions of the USA where the requisite data are available.

Development, Comparison, and Qualification of Predictive Pharmaceutical Stability Models Using Independent Statistical Tools - Mingkun Fu; Andrea Orta; Robert Bujalski; Jennifer Greene; Lakshminarasimhan Pranatharthiharan (Journal of Pharmaceutical Innovation, 2024)

Cerebrospinal fluid levels of 5-HIAA and dopamine in people with HIV and depression - Rong Fu; Hyder Jinnah; J. Lucas Mckay; Andrew H. Miller; Jennifer C. Felger; Eugene W. Farber; Sanjay Sharma; Neil Whicker; Raeanne C. Moore; Donald Franklin; Scott L. Letendre; Albert M. Anderson (Journal of NeuroVirology, 2023)

Ecophysiological and genomic analyses of a representative isolate of highly abundant Bacillus cereus strains in contaminated subsurface sediments - Jennifer L. Goff; Elizabeth G. Szink; Michael P. Thorgersen; Andrew D. Putt; Yupeng Fan; Lauren M. Lui; Torben N. Nielsen; Kristopher A. Hunt; Jonathan P. Michael; Yajiao Wang; Daliang Ning; Ying Fu; et al. (Environmental Microbiology, 2022)
Bacillus cereus strain CPT56D‐587‐MTF (CPTF) was isolated from the highly contaminated Oak Ridge Reservation (ORR) subsurface. This site is contaminated with high levels of nitric acid and multiple heavy metals. Amplicon sequencing of the 16S rRNA genes (V4 region) in sediment from this area revealed an amplicon sequence variant (ASV) with 100% identity to the CPTF 16S rRNA sequence. Notably, this CPTF‐matching ASV had the highest relative abundance in this community survey, with a median relative abundance of 3.77% and comprised 20%–40% of reads in some samples. Pangenomic analysis revealed that strain CPTF has expanded genomic content compared to other B. cereus species—largely due to plasmid acquisition and expansion of transposable elements. This suggests that these features are important for rapid adaptation to native environmental stressors. We connected genotype to phenotype in the context of the unique geochemistry of the site. These analyses revealed that certain genes (e.g. nitrate reductase, heavy metal efflux pumps) that allow this strain to successfully occupy the geochemically heterogenous microniches of its native site are characteristic of the B. cereus species while others such as acid tolerance are mobile genetic element associated and are generally unique to strain CPTF.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Rotor Tracking Using Phase of Electrograms Recorded During Atrial Fibrillation - Caroline H. Roney; Chris D. Cantwell; Norman A. Qureshi; Rasheda A. Chowdhury; Emmanuel Dupont; Phang Boon Lim; Edward J. Vigmond; Jennifer H. Tweedy; Fu Siong Ng; Nicholas S. Peters (Annals of Biomedical Engineering, 2017)

Patterns of AFLP variation in a core subset of cultivated hexaploid oat germplasm - Yong Bi Fu; Gregory W. Peterson; David Williams; Ken W. Richards; Jennifer Mitchell Fetch (Theoretical and Applied Genetics, 2005)